Cadre school-based elderly health assistance and screening for the prevention of non-communicable diseases - Nabillah Ainun Kusrinanti; Padma Fitriana Setyaningtyas; Hafiz Adhitama Hepni; Thoriq Naufal Adiba; Ginanjar Zukhruf Saputri; Woro Supadmi; Mila Abusri (University of Merdeka Malang, 2024)
Purwosari Village has a high prevalence of non-communicable diseases (diabetes mellitus and hypertension). Health cadres in Purwosari Village have been formed, however they are still not optimal, especially the knowledge and skills of cadres in preventing non-communicable diseases for the elderly. This service activity aims to increase the capacity of Purwosari Village “Posyandu” cadres regarding NCDs to improve the quality of life of the elderly in the surrounding area. The activity was carried out through a cadre school program with a lecture method for 2 offline sessions and continued with simulation for elderly posyandu cadres at the Purwosari Village, Kulonprogo. The activity is in partnership with Purwosari Village health cadres, the Girimulyo Public Health Promotion Team, and the Nasyiatul Aisyiyah Community of Kulonprogo. The activity was attended by a total of 67 cadres and 50 elderly posyandu cadres and 29 elderly people. The results of the activity showed an increase in the knowledge of cadres after education about non-communicable diseases prevention. The majority of cadres can understand the procedures for using and interpreting screening results. The elderly cadre school activities are effective in increasing the knowledge capacity regarding the prevention and monitoring of non-communicable diseases.